2016
DOI: 10.1007/s12223-016-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of dissimilatory Fe(III)-reducing bacteria from groundwater of the Siklós BTEX-contaminated site (Hungary)

Abstract: Dissimilatory iron-reducing bacteria are commonly found in microbial communities of aromatic hydrocarbon-contaminated subsurface environments where they often play key role in the degradation of the contaminants. The Siklós benzene, toluene, ethylbenzene, and xylene (BTEX)-contaminated area is one of the best characterized petroleum hydrocarbon-contaminated sites of Hungary. Continuous monitoring of the microbial community in the center of the contaminant plume indicated the presence of an emerging Geobacter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Microbial community analysis at a greater taxonomic resolution showed that both the freshly retrieved and incubated Fe(III)-coated and uncoated pumice slurries unamended with electron donors enriched for a close relative to Rhodoferax ferrireducens (6.4 and 5.8%, freshly retrieved; 15 and 2%, incubated with no electron donor; Figure 8). Similar to previous observations (Islam et al, 2004;Rowland et al, 2007;Hery et al, 2010;Zhuang et al, 2011;Farkas et al, 2017), electron donor addition altered the community diversity at the Genus level. Deployed Fe(III)-coated pumice slurries amended with electron donors enriched a higher population of Fe(III)-reducers (80% of the identified species) compared to the deployed uncoated pumice slurries amended with electron donors (31% of the identified species).…”
Section: Fe(iii)-reducers Captured By the Deployed "Microbe Baits"supporting
confidence: 89%
“…Microbial community analysis at a greater taxonomic resolution showed that both the freshly retrieved and incubated Fe(III)-coated and uncoated pumice slurries unamended with electron donors enriched for a close relative to Rhodoferax ferrireducens (6.4 and 5.8%, freshly retrieved; 15 and 2%, incubated with no electron donor; Figure 8). Similar to previous observations (Islam et al, 2004;Rowland et al, 2007;Hery et al, 2010;Zhuang et al, 2011;Farkas et al, 2017), electron donor addition altered the community diversity at the Genus level. Deployed Fe(III)-coated pumice slurries amended with electron donors enriched a higher population of Fe(III)-reducers (80% of the identified species) compared to the deployed uncoated pumice slurries amended with electron donors (31% of the identified species).…”
Section: Fe(iii)-reducers Captured By the Deployed "Microbe Baits"supporting
confidence: 89%
“…The high abundance of this bacterium in the groundwater of the Siklós site has been noted earlier (Farkas et al . 2017 ). However, aromatic hydrocarbon degrading capability of the type strain has not been tested, and it is currently not available in culture collections.…”
Section: Discussionmentioning
confidence: 99%
“… 2012 , 2013 ; Farkas et al . 2017 ) in Siklós, Hungary, in April 2015. Sediment samples were taken from the bottom of a monitoring well at 6 m below ground surface in the center of the contaminant plume (well ST-2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After ethanol precipitation, fragments were separated on a Model 3130 Genetic Analyzer (Applied Biosystems), while primary evaluation of electropherograms was performed using GeneMapper 4.0 software (Applied Biosystems). T-RFLP data were handled as described earlier (Farkas et al 2017). Cluster analysis (Jaccard and Bray-Curtis methods) of the T-RFLP electropherograms was performed using the PAST software package.…”
Section: Dna Isolation and T-rflp Fingerprintingmentioning
confidence: 99%